2010
DOI: 10.1002/elsc.201000064
|View full text |Cite
|
Sign up to set email alerts
|

The microcosm of a biogas fermenter: Comparison of moderate hyperthermophilic (60°C) with thermophilic (55°C) conditions

Abstract: An automated biogas fermenter running continuously for about two years using fodder and sugar beet silage as mono‐substrate without manure addition was analyzed simultaneously by amplified ribosomal DNA restriction analysis and microscopy. In this long‐term fermentation study, an oscillating population of prokaryotes was observed. The presence of most bacteria expected to be involved in hydrolysis of biomass via the anaerobic food chain was confirmed. In any case the methanogen population appeared more stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This is in accordance with previously published studies analyzing laboratory-scale biogas fermenters under controlled conditions [ 86 88 ]. In addition, [ 87 , 88 ] could show by automated fermentation with 'energy crops' as substrate that it was a reversible process between the dominance of Methanothermobacter spp. or Methanoculleus sp.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previously published studies analyzing laboratory-scale biogas fermenters under controlled conditions [ 86 88 ]. In addition, [ 87 , 88 ] could show by automated fermentation with 'energy crops' as substrate that it was a reversible process between the dominance of Methanothermobacter spp. or Methanoculleus sp.…”
Section: Discussionsupporting
confidence: 93%
“…The abundance of all these GBs was low in the samples examined. Species of the phylum Thermotogae were identified also in thermophilic biogas-production plants utilizing renewable primary products for biomethanation, even at low abundances [ 48 50 ]. Their role in utilization of complex carbohydrates has been recently suggested on the basis of the gene content of Defluviitoga tunisiensis [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Krakat, et al28 demonstrated that acetate and propionate in a fermenter with a long HRT of 26 days were only 7 mM and 1–2 mM, respectively. Therefore, except high temperature (>60°C), low HRT is also critical for the production of high fraction acetate in mixed culture CSTR.…”
Section: Discussionmentioning
confidence: 99%
“…It is should be noted that though high temperature could inhibit the activity of aceticlastic methanogens, acetate in the effluent also could be consumed by the syntrophic oxidation pathway. For example, Krakat, et al 28 demonstrated that acetate and propionate in a fermenter with a long HRT of 26 days were only 7 mM and 1–2 mM, respectively. Therefore, except high temperature (>60°C), low HRT is also critical for the production of high fraction acetate in mixed culture CSTR.…”
Section: Discussionmentioning
confidence: 99%